Telephone counselling in coping with the COVID-19 lockdown consequences: preliminary data - Macchiarulo, Elena; Branca, Francesco; Mallardi, Antonio; Costanza, Alessandra; Amerio, Andrea; Aguglia, Andrea; Serafini, Gianluca; Amore, Mario; Merli, Roberto (Acta Biomedica Atenei Parmensis, 2021)
The direct and indirect stressful effects of COVID-19 lockdown measures adopted to restrict population movements to help curb the epidemic impacted on people’s daily lives. Biella is a small Northern Italy province, historically characterized by the presence of an important and once flourishing textile industry. For decades this province has had suicide rates higher than the Piedmonts and Italian average. In two most recent decades a positive correlation between financial stressors, 2008 economic crisis related, and suicide has been found. As the current economic crisis COVID-19 related is expected to exacerbate again the vulnerability to suicide of this province, during the first lockdown the Crisis Center for Suicide Prevention of Biella set up a telephone counselling service. We aimed to evaluate whether it represented a suitable and useful tool for suicidal crisis prevention. Each phone intervention consisted of four phases: (i) psychoeducation, (ii) emotional stabilization, (iii) personal resources identification/reinforcement, (iv) session ending. This service provided a rapid therapeutic response to urgent requests for care, psychological support, and reassurance. It was able to mitigate stress and reinforce resilience in particularly vulnerable populations. The most innovative element of this project was that it proposed interventions for the emotional stabilization, something that is usually used in face-to-face sessions. Using the right protocols, it proved to offer continuity care and reduce pressure on hospital emergency departments while delivering good outcomes and patient satisfaction. Therefore, the COVID-19 pandemic provided an opportunity to overcome normative, technological, and cultural barriers regarding the use of remote healthcare services.